An examination of an outdoor pool's contributions to well-Being: predicting different dimensions of well-Being from the use of an outdoor community pool. Issue 3 (27th May 2021) - Ramos, William D.; Anderson, Austin R.; Middlestadt, Susan E.; Bhurosy, Trishnee
ABSTRACT: Health and well-being are integral components for achieving a good quality of life, with leisure engagement as a key component. This study investigated perceptions of dimensions of well-being from engaging at an outdoor pool obtained from 364 current users. Physical well-being reported the highest mean; with participants also reporting that the pool provided high levels of emotional and social well-being. While dimensions of well-being were related, correlations ranged from high (.765) between physical and emotional well-being to low (.351) between physical and occupational well-being. To explore differences between the dimensions of well-being, a regression analyses was used for predictions based on demographic and pool habit characteristics. Standardized regression weights revealed different characteristics predicted different types of well-being. Therefore, those managing recreational facilities like a community pool could consider more than how the facility promotes physical well-being and attempt to create spaces that promote other types of well-being.